2022
DOI: 10.3390/su142114511
|View full text |Cite
|
Sign up to set email alerts
|

Application of AHP and DEMATEL for Identifying Factors Influencing Coal Mine Practitioners’ Unsafe State

Abstract: Background: To effectively avoid accidents caused by practitioners’ unsafe state in the process of coal mine production processes, it is necessary to clarify the factors influencing the practitioners’ unsafe state, and take corresponding control measures accordingly. Methods: With the help of literature research and on-site interviews, grounded theory was used to construct the influencing factor index system of the coal mine practitioners’ unsafe state. The index system primary includes indices of four core ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Firstly, an assessment is conducted regarding the driver's professional proficiency, examining whether operational skills are reasonably mastered and if there is a sufficient level of safety awareness [73]. Secondly, the driver's professional evaluation is sought from colleagues and supervisors [74]. Additionally, reviewing relevant work logs and safety records is crucial to determining whether the driver consistently prioritizes safety [75].…”
Section: Standard For Determining the Level Of Psfs In The Cab Of Tow...mentioning
confidence: 99%
“…Firstly, an assessment is conducted regarding the driver's professional proficiency, examining whether operational skills are reasonably mastered and if there is a sufficient level of safety awareness [73]. Secondly, the driver's professional evaluation is sought from colleagues and supervisors [74]. Additionally, reviewing relevant work logs and safety records is crucial to determining whether the driver consistently prioritizes safety [75].…”
Section: Standard For Determining the Level Of Psfs In The Cab Of Tow...mentioning
confidence: 99%
“…Findings by Chen et al [25] showed that the factors affecting unsafe behaviors in mines could be classified into four categories: physiological, psychological, organizational, and technological. They introduced physical quality, fatigue level, safety attitude, safety awareness, and safety culture as the most important factors identified in these four categories.…”
Section: Literature Reviewmentioning
confidence: 99%